In vitro and in silico bioactivities and chemical profiling of Nepeta leucolaena to validate its use in nutraceutical or biopharmaceutical applications. (February 2023) - Mustafa, Shabnam; Nazir, Mamona; Riaz, Naheed; Saleem, Muhammad; Tauseef, Saba; Tousif, Muhammad Imran; Abbas, Zaheer; Kamran, Abdul Basit; Alaerjani, Wed Mohammed Ali; Alarfaji, Saleh S.; Muhammad, Shabbir; Zengin, Gokhan; et al.
Abstract: Nepeta leucolaena grows worldwide and is being used in folk medicine system without any scientific evidence. The present study was carried out to unveil the metabolic picture, biological potential and to valid the medicinal uses of N. leucolaena . The flowers and leaves of this plant were separately extracted with n -hexane, chloroform, ethyl, acetate and alcohol to get respective extracts. The total bioactive contents estimation disclosed that the highest value of phenolics (39.50 ± 0.53 mg GAE/g extract) and flavonoid (24.99 ± 0.53 mg GAE/g extract) in ethanolic extract of flowers and leaves, respectively. Further chloroform extract of flowers, and ethyl acetate extract of leaves also contain significant amount of phenolics. In DPPH free radical scavenging assay, only ethanolic extracts of flowers and leaves exhibited antioxidant activity with values of 49.02 ± 0.12 and 46.33 ± 0.10 mg TE/g extract, whereas, in ABTS free radical scavenging activity, in addition to ethanolic extract flowers (113.37 ± 0.07 mg TE/g extract) and ethanolic extract leaves (98.95 ± 0.57 mg TE/g extract), other extracts also showed moderate to weak activity. Highest metal reducing power was also associated with ethanolic extract of flowers and ethanolic extract of leaves (CUPRAC: 167.86 ± 3.57 and 151.76 ± 1.59 mg TE/g extract, respectively and FRAP: 108.30 ± 0.98 and 101.30 ± 0.32 mg TE/g extract, respectively), while other extracts also exhibited moderate activity. Almost equal (1.6 mmol TE/g extract) total antioxidant capacity was measured for ethanolic extract of leaves and flowers and n -hexane extract leaves, however, all fractions showed significant and comparable metal chelating activity with highest value was noticed for n -hexane extract flowers (25.99 ± 0.10 mg EDTA/g extract) and leaves (25.93 ± 0.79 mg EDTA/g extract). Similarly, all extracts showed nearly equal inhibitory activity against AChE (3.06–4.06 mg GALAE/g extract), while against BChE low polar extracts were more active with highest potential in n -hexane extract leaves (3.99 ± 0.20 mg GALAE/g extract) and chloroform extract of leaves (3.67 ± 0.48 mg GALAE/g extract). n -hexane extract of flowers displayed highest inhibitory contents against tyrosinase enzyme followed by ethyl acetate extract flowers and leaves. In anti-diabetic assays, the hexane extracts exhibited highest values against α-glucosidase (1.08 ± 0.006 and 1.05 ± 0.019 mmol ACAE/g extract, respectively) followed by ethyl acetate and chloroform extracts respectively. UHPLC-MS analysis of the ethanolic extract of the whole plant (Flowers and leaves together) helped to identify 139 compounds mostly of phenolic, flavonoid, steroids, terpenoids and glycoside classes of secondary metabolites. Docking studies of some of the major compounds against various enzymes substantiated the biological potential of N. leucolaena, and make it a potential ingredient to be used in several health promoting formulations. Graphical Abstract: ga1 Highlights: Nepeta leucolaena is a medicinal herb being used to cure various diseases in Gilgit-Baltistan region of Pakistan. Different extracts of N. leucolaena were found active and excellent source of antioxidant and enzyme inhibitors. UHPLC-MS analysis showed the presence of steroids, triterpenoids, saponins, alkaloids, phenolics and flavonoids. Insilico studies substantiated the bioactivities of N. leucolaena. N. leucolaena can be a promising source in disease-preventing nutraceutical or pharmaceutical applications.